Otimização: uma aplicação para desigualdade das médias e para desigualdade de Cauchy-Schwarz - Brito, Frank Werlly Mendes de (2016)
With the intention of offering an alternative to the Calculus to determine maximum and minimum values of functions, this academic paper explores the use of inequality between medium - exclusively for arithmetic and geometric - and the Cauchy-Schwarz inequality. Consists of statements, definitions and demonstrations of the validity of inequalities related before, the text aims to provide the necessary support for implementation of the thematic content optimization cases in geometry and some algebraic expressions. Such applicability is shown by discussing proposed and thoroughly resolved problems in order to provide for a solid understanding reader and the employability of the listed inequalities, even without knowledge of mathematical subjects at tertiary level, regarding the maximization and minimization issues values.